Takayasu Arteritis Presented with Unilateral Vision Loss : A Case Report - Jabed, Syed Md; Sharmin, Shaila; Ferdous, Md; Saha, Puja (IAHS Medical Journal, 2024)
Background: Takayasu Arteritis (TA) is a rare chronic granulomatous inflammation of the aorta or its branches and is prevalent all around the world. It causes stenosis of large arteries and ischaemic damage to target organs. There is usually a delay in recognising TA because of the rarity and unfamiliarity with the disease, unspecific early symptoms and lack of diagnostic equipment for early diagnosis. The purpose of the study to reminding readers of this issue and emphasize the necessity for further research on how to deal with in the best way. Case Report: We report a case of 30 years old male presented on 22nd August 2023 at Institute of Applied Health Sciences (IAHS) Chattogram with gradual loss of vision of left eye over a month accompanied by headache and later on diagnosed as a case of Takayasu’s Arteritis. Conclusion: Visual loss is the most common ocular symptom in Takayasu arteritis. Since a variety of causes may result in reduced vision in Takayasu arteritis. A careful history is very important to ascertain the cause of visual loss in Takayasu arteritis patients to reduce unnessary investigations and referrals. IAHS Medical Journal Volume 6(2) December 2023; 90-92